Celtic spirituality and the environment - Duncan, Graham (HTS teologiese studies, 2015)
Celtic spirituality has a long and distinguished ancestry with its origins in pre-Christian times. It was inculturated amongst peoples in the far west of Europe, particularly in Ireland, Scotland and the north and south west of England. It was different from Roman Christianity in distinct ways until the mid-7th century CE when Roman Christianity became the norm in Britain. It has experienced various revivals during the history of Christianity, with two contemporary expressions in New Age spirituality and Christian spirituality. From its inception, it has been closely linked to the environment.